Adsorption of Zn(II) on dialdehyde m-phenylenediamine starch - Liu, Jun-tao (Water science and technology : a journal of the International Association on Water Pollution Research, 2012)
A new chelating material dialdehyde m-phenylenediamine starch (DASMPA) was synthesized by reacting m-phenylenediamine with dialdehyde starch. The obtained material was characterized by element analysis and Fourier transform infrared (FT-IR) spectra. The FT-IR of DASMPA showed an absorption peak at 1605.95 cm(-1) indicating the formation of a Schiff base (C=N). Adsorption activity of DASMPA for Zn(2+) was also investigated in terms of contact time, pH, the initial Zn(II) concentration and temperature, the results revealed that pH = 5, t = 1 h were the optimal conditions. With the degree of substitution (DS) of the DASMPA increased, the adsorption capacity increased gradually. The adsorption equilibrium data correlated well with Freundlich isotherm. Moreover, lower temperature was preferable for the process as it was exothermic